A novel variability-based method for quasar selection: evidence for a rest-frame ∼54 d characteristic time-scale. Issue 1 (7th February 2014) - Graham, Matthew J.; Djorgovski, S. G.; Drake, Andrew J.; Mahabal, Ashish A.; Chang, Melissa; Stern, Daniel; Donalek, Ciro; Glikman, Eilat
Abstract: We compare quasar-selection techniques based on their optical variability using data from the Catalina Real-time Transient Survey (CRTS). We introduce a new technique based on Slepian wavelet variance (SWV) that shows comparable or better performance to structure functions and damped random walk models but with fewer assumptions. Combining these methods with Wide-field Infrared Survey Explorer mid-IR colours produces a highly efficient quasar-selection technique which we have validated spectroscopically. The SWV technique also identifies characteristic time-scales in a time series, and we find a characteristic rest-frame time-scale of ∼54 d, confirmed in the light curves of ∼18 000 quasars from CRTS, SDSS and MACHO data, and anticorrelated with absolute magnitude. This indicates a transition between a damped random walk and P ( f ) ∝ f −1/3 behaviours and is the first strong indication that a damped random walk model may be too simplistic to describe optical quasar variability.